Peningkatkan Hasil Belajar Pak Dengan Metode Pjbl Berbantuan LKPD Fase D Kelas VII SMP N 2 Silima Pungga Pungga - Manuren Simanullang; Timotius Tote Jelahu; Modestus Haryono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This classroom action research is motivated by the low value of Catholic religious education and character education. This study aims to improve learning outcomes by increasing students' interest in learning using project-based learning. This research was conducted on September 23 to September 28, 2024, in class VII of SMP Negeri 2 Silima Pungga Pungga. The type of research is Classroom Action Research with a pre-cycle and two cycles. The first cycle uses the PJBL method on the material I Have Ability. The second cycle uses the PJBL method on the material My Ability is Limited. In this study, the researcher used student worksheets (LKPD) as an assessment medium. The results of the study showed that with the project-based learning method, a pleasant learning atmosphere occurred so that student learning outcomes increased, namely from the pre-cycle results an average of 74.55% was obtained, from the results of cycle I an average of 81.41% was obtained and from cycle II an average of 87.66%. So in this study, a total increase from pre-cycle to cycle II was obtained of 13.11%. It is concluded that the problem based learning method can improve the learning outcomes of Catholic religious education and character.